Analysis of Factors Influencing User Interest in Adopting Fintech Robo-Advisor in Indonesia Using Utaut 2 - Zhafira, Faza Fariha; Rikumahu, Brady; Sugestie, Putri Fariska (International Journal Labs, 2025)
In Indonesia, robo-advisors were introduced around 2017, driven by the increasing penetration of internet usage and the adoption of digital technology in the financial sector. The use of robo-advisors grew significantly during the pandemic, as retail investors sought convenient ways to invest without the need for in-person meetings. Several fintech companies, including Bareksa, Bibit, and Moduit, offer wealth management services utilizing robo-advisor technology. While the total Assets Under Management (AUM) in Indonesia have increased, the growth rate of AUM has declined, which may indicate reduced new investment inflows. This study examines the factors influencing users’ intention to adopt fintech robo-advisor services in Indonesia, using the Unified Theory of Acceptance and Use of Technology (UTAUT 2) framework. The research is a quantitative descriptive study focusing on individuals in Indonesia who have used robo-advisor services via Bibit, Bareksa, or Moduit. Using purposive sampling, the study surveyed 150 respondents, with data analyzed through Partial Least Squares-Structural Equation Modeling (PLS-SEM). The study finds that all independent variables—performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, price value, and habit—significantly influence the adoption of fintech robo-advisors. Moreover, age, gender, and experience were identified as moderating factors. The strongest predictors of behavioral intention were performance expectancy, habit, and hedonic motivation, while habit, behavioral intention, and facilitating conditions were key drivers of use behavior. The study concludes that all factors significantly affect the adoption of fintech robo-advisors in Indonesia, and recommends that fintech companies leverage these findings to improve their features, communication strategies, and digital financial literacy initiatives.